Pertambahan bobot badan sapi impor Brahman Cross heifers dan steers pada bobot kedatangan yang berbeda - Amam Amam; Haryono Haryono (Jurnal Ilmu Peternakan Terapan, 2021)
The import of beef cattle to supply the national demand for meat has been regulated in the Regulation of the Indonesian Minister of Agriculture Number 108/Permentan/PD.410 /9/2014. This study aimed to assess the performance of imported cattle that came from Australia based on the Average Daily Gain (ADG). Observations were made on imported beef cattle from the Brahman Cross, which consisted of 2 types, namely heifers and steers. The focus of observation was on ADG of cattle with Come Weights (CW) ranging from 200, 300, and 400 kg. The imported cattle were fattened at the feedlot company for at least 106 days. The data obtained were analyzed descriptively and analyzed by independent samples test with the IBM SPSS Statistics 26 application program. The results showed that the maximum ADG of imported Brahman Cross cattle heifers at arrival weight (AW) 200, 300, and 400 kg were 2.01; 1.81; and 1.45 kg with an average ADG of 1.40; 1.17; and 1.10 kg, while the maximum ADG for this  steers type at arrival weight (AW) 200, 300, and 400 kg were 1.86; 2.53; and 1.96 kg with an average ADG of 1.44 each; 1.43; and 1.43 kg. The conclusion showed that the imported Brahman Crossbreeds of steers had a higher ADG than the heifers. Suggestions for feeder beef importing companies should choose the type of steers with an arrival weight (AW) of 300 kg, because cattle had the maximum potential of ADG.